2008
DOI: 10.1016/j.jas.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-element soil analysis: an assessment of its potential as an aid to archaeological interpretation

Abstract: Multi-element soil analysis is now an established technique in archaeology. It has been used to locate archaeological sites and define the extent of human activity beyond the structural remains, and to aid interpretation of space use in and around archaeological remains. This study aimed to evaluate the consistency of these soil element signatures between sites and hence their potential usefulness in archaeological studies. Known contexts on abandoned farms across the UK were sampled to test the relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(175 citation statements)
references
References 32 publications
5
160
0
3
Order By: Relevance
“…Wilson et al 2008). PXRF analysis of unprepared sediment samples can generate semi-quantitative concentration values of high-Z elements applicable for the chemical discrimination of different sediment layers.…”
Section: Coring Sediment Stratigraphy and Geochemistrymentioning
confidence: 99%
“…Wilson et al 2008). PXRF analysis of unprepared sediment samples can generate semi-quantitative concentration values of high-Z elements applicable for the chemical discrimination of different sediment layers.…”
Section: Coring Sediment Stratigraphy and Geochemistrymentioning
confidence: 99%
“…Archaeological sites have the potential to enhance or deplete levels of many stable nutrients due to the sites' history. Research has shown that elements such as Ba, Ca, Cu, P, Pb, Zn and Sr are often found in conjunction with archaeological activities (Wilson et al 2008). Little research has, however, been directed at the implications of these geochemical variations from an agronomic point of view.…”
Section: Soil Geochemistrymentioning
confidence: 99%
“…Background variation linked to differences in soils can result in patterns of element concentration unconnected to the archaeology. 1 …”
Section: Geochemical Correlationmentioning
confidence: 99%
“…The abandonment of human activities in settlements does not affect chemical residue remains in soils. The potential validity of the chemical analysis of soil to interpret archaeological finds lies in its ability to predict significant features based on (i) the chemical signatures of total concentrations of multielements such as Ba, Ca, P, Zn, Cu and Pb in soils; 1 (ii) the chemical signatures of floor samples in the Maya region; 2,3 (iii) the available nutrients in soils from the Brazilian Amazon basin, [4][5][6][7][8] known by designations such as black earth, Indian black earth, anthropogenic black earth, archaeological black earth, Amazonian black earth (ABE) 9,10 or Amazonian dark earths. 11,12 The area in which ABE occurs is characterized by well-drained soil, running water and located in a particular geographical setting from which the surrounding areas can be clearly observed.…”
Section: Introductionmentioning
confidence: 99%